2018
DOI: 10.2147/clep.s164556
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of primary brain tumors in cochlear implant patients in Sweden between 1989 and 2014

Abstract: PurposeCochlear implants are widely used for hearing rehabilitation of deaf children with congenital deafness or adults with acquired severe-to-profound hearing loss. The sound processor antenna creates a radio frequency-electromagnetic field transmitting the sound signal to the implant, similar to that in a mobile phone. A recent case report suggested a relationship between cochlear implants and malignant glioma, and some epidemiological studies have suggested an increased glioma and acoustic neuroma risk ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Our findings suggest that although the current allowable mobile phone radiation level is very low, it may be sufficient to induce biological effects. Some studies [ 82 , 92 , 93 ] have reported that existing data are not sufficient to support the assumption that tumors are caused by mobile phone usage. Thus, determination of whether these effects might cause any significant health effects requires further investigation, especially with respect to neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that although the current allowable mobile phone radiation level is very low, it may be sufficient to induce biological effects. Some studies [ 82 , 92 , 93 ] have reported that existing data are not sufficient to support the assumption that tumors are caused by mobile phone usage. Thus, determination of whether these effects might cause any significant health effects requires further investigation, especially with respect to neoplasms.…”
Section: Discussionmentioning
confidence: 99%